1993
DOI: 10.1042/bj2950549
|View full text |Cite
|
Sign up to set email alerts
|

Histone H4 stimulates glucose transport activity in rat skeletal muscle

Abstract: We investigated the effects of purified histone H4 on glucose transport activity in rat soleus and flexor digitorum brevis muscles. Histone H4, at concentrations up to 11.8 microM, increased 2-deoxyglucose (2-DG) uptake in a dose-dependent fashion. However, at concentrations higher than 11.8 microM, H4 caused a decrease in 2-DG uptake from the maximum, suggesting a secondary inhibitory action of this compound. The maximal effect of H4 on 2-DG uptake was not additive to the maximal effect of insulin. Moreover, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The surface expression of these proteins was often found associated with cell activation [25,26,28,30], or is relevant to egg fertilization [29], which involves cell ionic events. H2A and H2B have a primary structure identical with those of the homoeostatic thymus hormones HTH a and HTH b respectively [22,23], and the ovarian gonadotropin-releasing hormone-binding inhibitor was identified as H2A [54].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The surface expression of these proteins was often found associated with cell activation [25,26,28,30], or is relevant to egg fertilization [29], which involves cell ionic events. H2A and H2B have a primary structure identical with those of the homoeostatic thymus hormones HTH a and HTH b respectively [22,23], and the ovarian gonadotropin-releasing hormone-binding inhibitor was identified as H2A [54].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested a hormone-like activity for some histones ( [22] ; see [23] for additional references), and hypothesized additional functions for histones apart from being nucleosoma components [24]. Histones, or proteins resembling them, have been shown to be present on the surface of various cell types [25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation